PERENCANAAN STRUKTUR CONVENTION HALL KOTA MARTAPURA KALIMANTAN SELATAN - Nandia Tri Pangestika; Dika Dwi Angga; Sri Tudjono; Himawan Indarto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Design structure of this building by SNI 03-1726-2010 on this final report are designed inseismic zoning area of Martapura city using the structure frame system method with configuration structure System Bearer Special Moment (SRPMK). The System Bearer Special Moment (SRPMK) election expected to be a story building structure behave ductile, because structureis ductile energy dissipation capacity were large and has a good carrying capacity in the resist earthquake loads. This system is planned to use the concept of strong column weak beam, where the vertical elements of the structure (column) should be stronger than the horizontal elements of the structure (beam), to be plastically formed jointsfirst on the beam. The joints meeting of the beam-column should also be well designed to avoid collapse first. The analysis of the structure of the building by SNI 03-1726-2010 using SAP software help v10 2000 with the results of the analysis are used to determine the fundamental period of the structure and the forces acting on the structure. Fundamental structural period must be limited so that the structure is not very flexible. Results in the forces acting on the structure is used to design the structure of the building.